INDIGENOUS STATE AND REGIONAL CONFLICTS: PROBLEMS TO IMPLEMENT THE CONSTITUTION IN BOLIVIA - Gamboa Rocabado, Franco (2013)
This article analyzes the main problems that the new Political Constitution of Bolivia is facing before being implemented, once it was approved on February 2009. In addition, it is also analyzed how the constitutional provisions were negotiated in order to make the constitutional referendum viable. What were the political conflicts in the critical juncture 2008-2009, and what kind of reflection should be considered as to how the new emerging regional and local governments – together with its decentralized structures-are able to renew democracy in Bolivia within the framework of the Plurinational State? The multiple challenges ahead are highly difficult to confront from the perspectives of the democratic theory.